2018
DOI: 10.1007/s00586-018-5686-x
|View full text |Cite|
|
Sign up to set email alerts
|

Right infraaxillary thoracotomy approach for upper thoracic vertebral decompression and fusion at T2–T6 levels: a technical note

Abstract: The technique described is a safe and novel right infraaxillary thoracotomy approach to provide direct access from vertebral bodies T2-T6 and to provide adequate room for upper thoracic vertebral decompression and fusion surgery. However, a suitable fixation implant should be designed. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Moreover, anatomical critical structures such as the common carotid trunk, the jugular vein or trachea are not encountered, hence increasing the safety of the procedure. In the latest work of Liu et al, a similar approach was reported [1]. However, in this work, an 8-12-cm right-sided infraaxillary incision was applied.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, anatomical critical structures such as the common carotid trunk, the jugular vein or trachea are not encountered, hence increasing the safety of the procedure. In the latest work of Liu et al, a similar approach was reported [1]. However, in this work, an 8-12-cm right-sided infraaxillary incision was applied.…”
Section: Discussionmentioning
confidence: 95%
“…The most common approaches include the anterior supramanubrial (Smith Robinson), transmanubrial, and transsternal as well as the posterior approach with costotransversectomy [2]. Recently, an infraaxillary rightsided thoracotomy was described for upper thoracic vertebral decompression and fusion at T2-T6 levels [1]. In the current case, we report a transaxillary left-sided mini-thoracotomy for thoracic vertebral resection and reconstruction at T2-T3 levels.…”
Section: Introductionmentioning
confidence: 85%
“…At that level a resection of the 4 th arch is performed, therefore the anterior face is exposed to the vertebral bodies from T2-T6. 19 The second surgical technique consists in a left axillary approach at the level of the second costal arch with an incision of 4 cm of length, creating a safe access route to the anterior and lateral face of T2-T4 vertebrae, allowing the vision of all the structures surrounding the vertebral body, 20 it is important to mention that both approaches avoid the high complexity and comorbidities of a sternotomy, which confirms by means of adequate familiarization with the approach or the help of a thoracic surgeon, it can be performed either right or left depending on the pathology of each patient. Based on the above, it is likely that a high right infraclavicular anterior thoracic route such as the one described in our case is less complex for the thoracic surgeon or spinal surgeon since we avoid dissection of the mediastinum.…”
Section: Discussionmentioning
confidence: 99%